Uncovering challenges mainland Chinese international students face in English language communication in Malaysian higher education institutions - Xiuwen, Zhai; Razali, Abu Bakar (Universiti Teknologi MARA, 2022)
Since establishing the Silk Road initiatives, Malaysia, as a significant ASEAN country with top-ranked universities in QS, has become one of the most popular Edu-hubs for mainland Chinese international students to pursue further studies. This qualitative case study explored mainland Chinese international students’ challenges in English communications through interviews. The data were sorted into three categories: academic oral English communication challenges, the factors causing these challenges, and the methods to solve these challenges. Qualitative data were collected through three sessions of in-depth individual interviews. Informants were six mainland Chinese international students (three master’s students and three Ph.D. students) from a public university in Klang Valley, Malaysia. The data were analysed using the thematic analysis method. This study discovered the challenges in English communication by mainland Chinese international students, for example, insufficiency of social and linguistic competence of using appropriate words. This research also identified the factors that contribute to these challenges,for example, insufficient exposure to actual English communication settings. The researchers also investigated the strategies used by these students to overcome these challenges,for example, undergoing oral English training, prior preparations, and self-learning methods. The findings contribute to the improvement of international education services for Malaysian higher education institutions.